Preparation and characterization of Biochanin A loaded solid lipid nanoparticles - Tao1,2,3, Chunlei; Cheng4, Hailin; Zhou1, Kai; Luo1, Qing; Chen1,2,3, Weidong (Asian Journal of Pharmaceutics (AJP), 2014)
Biochanin A, the predominant isoflavones found in plants, had proved its human health benefits. The purpose of this research was to study whether Biochanin A (BCA) loaded solid lipid nanoparticles (SLN) could improve solution and prolong the halfâ€life of BCA. BCAâ€SLN was prepared by emulsion evaporation and low temperature solidification technique, and freezeâ€dried powders were developed to improve stability.The mean particle sizes, zeta potential, entrapment efficiency (EE), and drug loading capacity (DL) of BCA was 176.0 nm, âˆ’18.7 Â± 0.26, 97.15 Â± 0.28%, and 6.38 Â± 0.04%, respectively. The results of differential scanning calorimetry (DSC) and Xâ€ray diffraction analysis (XRD) indicated that the BCA was wrapped and absorbed in the nanoparticles. The solution of preparation is much higher than the untreated BCA.Results of stability of SLN showed a relatively shortâ€term stability after storage at 4Â°C and 25Â°C for 15 days. Drug release of untreated BCA and BCAâ€SLN was fit into the Biexponential equations and Weibull equations, respectively, and SLN showed sustained release properties. But after freezeâ€dried, stability was improved, and the EE and DL had a slightly decrease. The mean particle size was slightly increased, but the structure was not changed. In conclusion, SLN systems can represent an effective strategy to change the poor aqueous solubility and prolong the halfâ€time of BCA.